2021
DOI: 10.1016/j.jvs.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in vascular surgery during the coronavirus disease-2019 pandemic: A multisite healthcare system experience

Abstract: Objective To assess the introduction of telemedicine as an alternative to the traditional face-to-face encounters with Vascular Surgery patients in the era of the Coronavirus Disease 2019 (COVID-19) pandemic. Methods Retrospective review of prospectively collected data on face-to-face and telemedicine interactions at a multi-site health care system from January to August 2020 in Vascular Surgery patients during the COVID-19 pandemic. The end point is direct patient sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…In general, patient and clinician satisfaction with telemedicine is high [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. While convenience factors, including travel-related time and cost savings, contribute to patient satisfaction [ 19 ], patients have also rated highly the quality of communication and patient-centeredness experienced in telemedicine visits [ 6 , 20 ].…”
Section: Personalized Medicine: Benefits Offered By Telemedicinementioning
confidence: 99%
“…In general, patient and clinician satisfaction with telemedicine is high [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. While convenience factors, including travel-related time and cost savings, contribute to patient satisfaction [ 19 ], patients have also rated highly the quality of communication and patient-centeredness experienced in telemedicine visits [ 6 , 20 ].…”
Section: Personalized Medicine: Benefits Offered By Telemedicinementioning
confidence: 99%
“…Erben and colleagues 15 aimed to evaluate telemedicine visits' satisfaction rate for patients who received vascular surgery during the COVID-19 outbreak. Most of the questionnaire respondents (80.6%) rated that their healthcare experience with telemedicine encounters was "very good."…”
Section: Discussionmentioning
confidence: 99%
“…Erben and colleagues 15 aimed to evaluate telemedicine visits’ satisfaction rate for patients who received vascular surgery during the COVID-19 outbreak. Most of the questionnaire respondents (80.6%) rated that their healthcare experience with telemedicine encounters was “very good.” The authors noted that the high quality of patients’ satisfaction and healthcare experience remained unchanged compared to prepandemic face-to-face traditional care delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The trainee surgical volume has also decreased by 86.4% for the vascular surgery fellow. In contrast, a multisite health care system study from Mayo clinic in USA reported that 12.6% of the total vascular surgery encounters were completed via telemedicine between March 2020 and August 2020 [ 12 ]. Approximately 81% of these patients rated their overall healthcare experiences ‘very good’ and this rating was comparable to face-to-face encounters (79%) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teleconsultation still has many challenges including reimbursement, accessibility, monitoring of quality, patient confidentiality, local and national legal oversight and liability, Internet speed, patients’ educational and know-how computer literacy level [ 12 , 16 ]. Although there are multiple reports on the utilization of telemedicine services in different specialties worldwide, there is a paucity of studies from the Middle East [ 17 ] and the unique social and legal parameters which could affect clinical best practice.…”
Section: Discussionmentioning
confidence: 99%